Postnatal mother: Knowledge and attitude towards Neonatal Jaundice (NNJ) - N. Said,; N. Ashikin; Mahfuzah .; SH Zuraidah; Norhaini .; M. Ramadan (Faculty of Nursing, Universitas Andalas, 2018)
Background: Neonatal jaundice (NNJ) is a pathological situation where an imbalance between bilirubin production and excretion is present due to a multitude of factors. Purpose: To identify the number of post-natal mothers who had received education and their attitude on neonatal jaundice. Method: A cross-sectional design was carried out among 131 posts natal mother. The questionnaire was given to the respondents. Results: Results show there is a significant relationship between knowledge and attitude towards neonatal jaundice among postnatal mother. A part 50% of the mothers have a neutral attitude, 27.5% have a positive attitude and 8.4% have a negative attitude towards neonatal jaundice. Conclusion: The out-come of this study showed that most of them others have good knowledge on neonatal jaundice. However, they may fear invasive procedures such as taking blood from their baby. Future studies should focus on attitude towards traditional treatments among postnatal mothers.